Study on Intelligent Early Warning System of Railway Locomotive Driver Operation State - QU Surong; ZHANG Zhongyang; ZHANG Xianfeng (机车电传动)
In order to solve the online real-time monitoring problems on railway locomotive driver operation state, face image tracking and human pupil biological image recognition technology was applied, and vehicle intelligent detection device, data transmission system and ground on line analysis system was designed. Through the system software coordinated control, the locomotive driver operation state intelligent early warning system was constructed, which realized automation on the all-weather online real-time tracking monitoring, early warning, analysis and intervention.